Early initiation of ambroxol treatment diminishes neurological manifestations of type 3 Gaucher disease: A long-term outcome of two siblings. (May 2021) - Ramadža, Danijela Petković; Zekušić, Marija; Žigman, Tamara; Škaričić, Ana; Bogdanić, Ana; Mustać, Gordana; Bošnjak-Nađ, Katarina; Ozretić, David; Ohno, Kousaku; Fumić, Ksenija; Barić, Ivo
Abstract: Gaucher disease type 3 (GD3) is a severely debilitating disorder characterized by multisystemic manifestations and neurodegeneration. Enzyme replacement therapy alleviates visceral signs and symptoms but has no effect on neurological features. Ambroxol has been suggested as an enzyme enhancement agent. Some studies have confirmed its effectiveness in preventing the progression of neurological manifestations of neuronopathic Gaucher disease. In this study, we report two GD3 siblings in whom ambroxol combined with enzyme replacement therapy was initiated at different stages of the disease. We demonstrate the enzyme enhancement effect of ambroxol on L444P/H225Q;D409H glucocerebrosidase activity through results of fibroblast studies and long-term clinical outcomes of the two patients. The sibling diagnosed at the age of four-and-a-half years with significant neurological involvement manifested relatively rapid improvement on ambroxol treatment, followed by stabilization of further course. The younger sibling, in whom the treatment was started at seven weeks, displayed attention deficit and low average cognitive functioning at the age of seven years, but did not manifest other neurological symptoms. The difference in neurological outcomes indicates that ambroxol delayed or even halted the evolution of neurological manifestations in the younger sibling. This observation suggests that early initiation of ambroxol treatment may arrest neurological involvement in some GD3 patients. Highlights: Ambroxol has a chaperone effect on L444P glucocerebrosidase in fibroblast culture. Ambroxol modifies progression of neurological involvement in Gaucher disease type 3. Early initiation of ambroxol treatment may prevent neurodegeneration.